Model comparison of estimated glomerular filtration rate for acute kidney injury in intensive care unit - Dzaharudin, Fatimah; Jamaludin, Ummu Kulthum; Md Ralib, Azrina; Mat Nor, Mohd Basri; Tumian, Afidalina; Ismail, Amelia Ritahani (IOP Publishing Ltd., 2020)
Acute kidney injury (AKI) is common in critically ill patients and often associated with higher mortality. It is commonly diagnosed using plasma creatinine, a fluid eglomerular filtration. In this study, we analysed the highly nonlinear and complex behaviour within human systems of estimating glomerular filtration rate in critically ill patients to estimate AKI outcome by developing an application program that describes various numerical mathematical models estimated glomerular filtration rate (eGFR). The program was developed to collect numerous clinical patient data and perform computations of the governing equations that may provide clinicians with rapid estimation of GFR which allow prediction of recovery or worsening of renal function at bedside. Data collection using the application program was conducted at the intensive care unit in Kuantan, Malaysia from January to August 2016. It was found that the eGFR by CKD-EPI shows the best correlation with kinetic GFR (keGFR) equations compared to other mathematical methods for Malaysian ICU patients. It is endeavoured that more patient data would be collected using this mobile application, to develop a more accurate GFR estimation model suitable for Asian populations since creatinine based equations are often derived based on white populations.